PENERAPAN METODE RESITASI DALAM PEMBELAJARAN KETERAMPILAN MENULIS BAHASA JERMAN KELAS XI BAHASA SMA NEGERI 13 SURABAYA - R A IDUS, MELANIA (LATERNE, 2016)
In the German language learning students must master the four language skills, namely skills of listening, speaking, reading and writing. Among the four skills of writing skills is one aspect of language skills that are important and complex and is considered difficult as compared with the other  language skills. Writing skills needed to express ideas or thoughts writer. One method that can be used in German language writing skills is the Recitation method. Recitation method is a method which is conceived as a way of learning that is done by giving assignments to the students. The stages of Recitation method are, the first stage is the stage of assignment,  the second stage is the stage of implementation of the tasks and the third stage is the stage of account for tas. With the recitation teacher guidance can be given directly, if students have difficulty, other than that after completing the task, the students report the results to the teacher to be votes.   Formulation of the problem in this research is how the student learning outcomes by applying the Recitation method in learning German Language writing skills on Class XI Language of SMAN 13 Surabaya. The purpose of this study was to describe the results of student learning by applying Recitation method in learning German Language writing skills on Class XI Language of SMAN 13 Surabaya.  The design of this study used a qualitative approach while the method used is descriptive method. By using research instruments that form the task of writing a personal letter in German on a class XI Language of  SMAN 13 Surabaya. Based on the survey results revealed that the recitation method can improve learning outcomes in learning the German language writing skills student on class XI language of SMAN 13 Surabaya, seen from the increasing value of the first  task until the last task. The results of the first tasks that the average value of the class is 79.16, while the second task giving an average value of students has risen 87.5 and in the delivery of the third task also increased value is an average of 92.04 students. The average value increased student mastery of the material is supported by increasing anyway Keywords: Recitation method, writing skills.